2013
DOI: 10.1007/s10753-013-9775-z
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum Levels of Th2-Related Chemokine CCL22 in Women Patients with Multiple Sclerosis: A Comparison Between Patients and Healthy Women

Abstract: Chemokines play a major role in autoimmune diseases such as multiple sclerosis (MS). Gender also affects the susceptibility and course of MS. The aim of this study was to investigate the serum levels of the macrophage-derived chemokine (CCL22) in women and men patients with MS. Blood samples were collected from 135 healthy subjects (35 men and 100 women) and 135 MS patients (29 men and 136 women; 47 newly diagnosed and 88 treated patients and have relapsing-remitting (RRMS; n = 65), secondary progressive (SPMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…CCL22, a member of the CC chemokine families, is mainly produced by monocyte‐derived macrophages and DCs upon stimulation with microbial products . A recent study has reported that the mean serum levels of CCL22 in newly diagnosed patients with multiple sclerosis were significantly lower than those in treated patients with multiple sclerosis and healthy people, suggesting that CCL22 serves as a biomarker for autoimmune diseases. However, the roles of CCL22 in the regulation of immune homeostasis by apoptotic cell clearance are poorly defined, although impairment of apoptotic cell phagocytosis causes autoimmune diseases .…”
Section: Discussionmentioning
confidence: 99%
“…CCL22, a member of the CC chemokine families, is mainly produced by monocyte‐derived macrophages and DCs upon stimulation with microbial products . A recent study has reported that the mean serum levels of CCL22 in newly diagnosed patients with multiple sclerosis were significantly lower than those in treated patients with multiple sclerosis and healthy people, suggesting that CCL22 serves as a biomarker for autoimmune diseases. However, the roles of CCL22 in the regulation of immune homeostasis by apoptotic cell clearance are poorly defined, although impairment of apoptotic cell phagocytosis causes autoimmune diseases .…”
Section: Discussionmentioning
confidence: 99%
“…The role of Th2 cells, which secrete high levels of IL-4, IL-5, and IL-13, remains controversial (Raphael et al 2015). We have previously observed the elevated concentrations of a Th17-related chemokine (CCL20), diminished levels of a Th2/Treg-related chemokine (CCL22), and unchanged levels of a Treg-related cytokine in patients with MS (Jafarzadeh et al 2014a;Jafarzadeh et al 2014b;Jafarzadeh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CCL22 plays an important role in a variety of other diseases, including allergic rhinitis (76), atopic dermatitis (77), and lymphoma (78). Recent studies suggested that CCL22 can be used as a biomarker for autoimmune diseases (79). On the other hand, the role of CCL 22 in regulation of immune homeostasis is unclear (80,81).…”
Section: Discussionmentioning
confidence: 99%